Role of Pioglitazone with Metformin or Glimepiride on Oxidative Stress-induced Nuclear Damage and Reproductive Toxicity in Diabetic Rats - Rabbani, Syed Imam (Penerbit Universiti Sains Malaysia, 2010)
BACKGROUND: Oxidative stress due to improper control of blood glucose in chronic diabetes plays a major role in the development of secondary complications including cancer and birth defect. The aim of this study is to evaluate the protective effect of combination of pioglitazone with metformin or glimepiride against the experimental type-2 diabetes induced nuclear damage and reproductive toxicity in rats. METHODS: The combinations of Pioglitazone (Pio-1 mg/kg) with metformin (Met-50 mg/kg) or glimepiride (Gmp-0.2 mg/kg) given orally daily for 4 weeks were tested against nicotinamide (NA-230 mg/kg, ip)-streptozotocin (STZ-65 mg/kg, ip)-induced micronuclei (MN) formation and sperm abnormalities in male Wistar rats. The antioxidant status was evaluated by measuring the levels of serum lipid peroxidation (LPO), catalase (CAT) and superoxide dismutase (SOD). RESULTS: The administration of Pio+Met significantly (P<0.01) reduced the number of micronucleated erythrocytes, increased the polychromatic: normochromatic erythrocytes (P/N ratio), reduced (P<0.001) sperm morphology defects and increased (P<0.05) the caudal sperm count compared to the untreated diabetic condition. Furthermore, the Pio+Met combination enhanced the antioxidant status in diabetic animals. However, Pio+Gmp did not attenuate the nuclear and sperm defects or oxidative stress. CONCLUSIONS: The observations suggest that Pio+Met combination reduced nuclear damage and sperm abnormalities by enhancing the antioxidant status in the diabetic animals.